2009
DOI: 10.1002/hed.21001
|View full text |Cite
|
Sign up to set email alerts
|

Function, postoperative morbidity, and quality of life after cervical sentinel node biopsy and after selective neck dissection

Abstract: Functional outcome after SNB is significantly better than after SND; however, this is not reflected in the scores of QOL questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
157
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(177 citation statements)
references
References 46 publications
9
157
1
4
Order By: Relevance
“…Thus, SNB reduced the rate of secondary neck metastasis and increased the 5-year OS rate. Other studies reported a 5-year OS rate of 80% and a 2-year OS rate of 87-90%; our results are superior to those findings (3,18,20,21), suggesting that SNB is an effective approach in cN0 early OSCC. However, there have been few previous reports comparing excision alone to excision with SNB.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…Thus, SNB reduced the rate of secondary neck metastasis and increased the 5-year OS rate. Other studies reported a 5-year OS rate of 80% and a 2-year OS rate of 87-90%; our results are superior to those findings (3,18,20,21), suggesting that SNB is an effective approach in cN0 early OSCC. However, there have been few previous reports comparing excision alone to excision with SNB.…”
Section: Discussioncontrasting
confidence: 95%
“…In other reports, the NPV and false-negative rates were 90-96 and 2.5-22%, respectively (3,10,18,20,21). In the present study, the NPV and false-negative rates were 94 and 18%, respectively, which were similar to previously reported rates.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the main pitfall of this strategy is that histopathological diagnosis based on serial sections with immunohistochemistry (SS-IHC) is far too time consuming to be made use of during surgery in routine practice (van Diest et al, 2001). A delayed pN diagnosis compels pN þ patients (up to 40% of cases) to undergo further additional surgery with an increased risk of post-operative complications and a damaged functional outcome (Kuntz and Weymuller, 1999;Schiefke et al, 2009). In this context, real-time reverse transcriptase-PCR (RT -PCR) may be helpful because it is operator independent and, with some adaptation, can be automated and rapidly performed (Raja et al, 2002;Hamakawa et al, 2004).…”
mentioning
confidence: 99%